Sworn Translators’ and Interpreters’ Assessment. Literature Review and Analysis of the Information of Candidates for Certification and Recruitment Examinations - Ordóñez López, PIlar (Íkala, Revista de Lenguaje y Cultura, 2009)
This article sets out to reveal the lack of standardisation and rigour in the field of translation assessment and its implications on candidates for translator’s certification or recruitment examinations. A brief review of translation assessment literature is followed by a practical analysis of the information provided to candidates in three different examination procedures: examinations for the certification as a Sworn Translator, organised by the Spanish Ministry of Foreign Affairs; examinations for the Chartered Institute of Linguists “Diploma in Translation;” and recruitment competitions for translators in the European Commission.